A Vicious Cycle of Regional Unemployment and Crime? - Evidence from German Counties - Tim Umbach (ZBW - Leibniz Information Centre for Economics, 2020)
Much research has been done showing that unemployment can cause crime, and that crime adversely impacts economic activity. However, very few authors have considered a simultaneous relationship. Using an IV-setup and regional panel-data, I find evidence for the possibility of a vicious cycle, with unemployment leading to higher crime rates and crime rates raising unemployment. I further find that especially employment in low-skill service jobs is adversely affected by crime, that many types of crime are impacted by unemployment differently and that both apartment rents and GDP-growth decrease if crime increases. The spatial dependencies found further raise the possibility that these vicious cycles could spill over into neighboring regions.
Keywords: J21; J32; K42; R11; R23; R30; 330; Crime; Unemployment; Amenities; spatial autregresssive model; SARAR; endogenous regessors.